PENGARUH PENAMBAHAN SERBUK JAHE MERAH (Zingiber officinale Var. Rubrum) TERHADAP TEH HASIL KEMPAAN DAUN GAMBIR (Uncaria gambir Roxb) - Putra Bungsu, Iseng Maijen; I Ketut Budaraga; Nita Yessirita (Fakultas Pertanian, Universitas Ekasakti, 2021)
This study aims to determine the effect of adding red ginger powder to the compression results of gambier leaves and the addition of the right addition of ginger powder to meet the requirements of red ginger gambir leaf tea which is the most preferred by consumers. This research has been conducted at the Laboratory of Agricultural Products Technology, Ekasakti University, Padang. From October to November 2020. The design used in this study was a simple completely randomized design (CRD) with 5 treatments and 3 replications. The results of the observation were analyzed using ANOVA and Duncan's New Multiple Range Test (DNMRT) advanced test at 5% level. The results showed that the addition of ginger powder had a very significant effect on water content, ash content, polyphenol content and all test parameters met the dry quality requirements set by SNI. The tea produced by compressed red ginger gambir leaves that the panelists liked the most was treatment E (addition of 40% red ginger powder).